Unravelling ethical dilemmas: how consultants’ decisions impact road construction project performance in Dar es Salaam and Tabora, Tanzania - Herry A. Mwankusye; Paul Nsimbila; Edward Makoye (Eastern African Journal of Humanities and Social Sciences)
This study examines how consultants' decisions, shaped by ethical dilemmas, influence the performance of road construction projects in Tanzania. Grounded in the Virtue Theory of Ethics, the research explores the role of behavioural, socio-economic, institutional, and political factors in shaping ethical decision-making within the construction sector. The study employs Covariance-Based Structural Equation Modelling (CB-SEM) to analyse 289 valid survey responses from road construction professionals. The measurement model was validated using factor loadings, while the structural model assessed the relationships between ethical dilemmas and project performance. The findings reveal that institutional factors have the most significant influence on ethical dilemmas in road construction, followed by behavioural factors, socio-economic factors, and political factors. The regression model confirms that ethical dilemmas significantly impact project performance, with governance structures, transparency, and professional integrity emerging as key determinants. The ANOVA test further confirms the statistical significance of the model, reinforcing the robustness of the relationship between ethical dilemmas and construction project outcomes. The study calls for policy reforms to strengthen ethical governance in road construction. Regulatory bodies should enforce stricter accountability measures, promote ethical leadership training, and integrate digital transparency tools. Practitioners should adopt ethics audits, stakeholder engagement frameworks, and integrity-driven decision-making to enhance project success. This study provides empirical evidence on the structural relationship between ethical dilemmas and project performance, offering a novel perspective on fostering ethical character and professional integrity in the industry. The findings inform policymakers, practitioners, and researchers on improving ethical compliance and infrastructure sustainability.